Perancangan Framework Peningkatan Kualitas Informasi Melalui Perbaikan Proses Produksi Informasi - Fathonah Tri Hastuti; Albarda Albarda (Innovation in Research of Informatics (INNOVATICS), 2020)
Government requires the mapping of the country in order to make the development can be precisely targeted and evenly. Government agencies that the function is to perform the data collection in this country is the Statistics of Indonesia (BPS). To answer the complexity problems faced by the government or private, BPS is expected to improve the quality of information produced. To improve the quality of information, the necessary framework that can be used as a guide in measuring and improving the quality of information is needed. The proposed framework in this research was carried out based on study literature. The quality of information was assessed during the information production process. The information production process was improved based on the maturity and attributes concept in COBIT 4.1. The main purpose of this research is to design a framework that is able to provide guidance to improve the quality of information in the form of recommendations for information production improvement.